Waste Reduction in Electrical Production Process in PT Petrokimia Gresik Coal Utility Using Value Stream Mapping and FMEA Applications - Rosyid Ridlo; Mokh. Suef (IPTEK Journal of Proceedings Series, 2020)
Unit Utilitas Batu Bara (UBB) is one of the power plants owned by PT Petrokimia Gresik which began operating in 2010. UBB consists of a steam boiler with a capacity of 2x150 tons per hour and a power plant with a capacity of 25 megawatt. There is waste in the electricity production process at UBB which is indicated by the value of actual efficiency is low compared to the value of efficiency in the design and performance test. This research discusses efforts to reduce waste in the process of steam and electricity production in UBB by making value stream mapping, identifying waste, conducting root cause analysis, and making FMEA. Through data collection and processing, interviews with expert employees at UBB, as well as comparing reference activities and actual activities, obtained that waste occurs in coal out from coal mill, boiler water, and boiler efficiency. Through analysis 5 whys, obtained fifteen root causes of waste. Through the calculation of events, severity, and detection the risk priority number is obtained. Based on the existing critical risks, through the collection of FMEA worksheets, an estimate of actions to reduce waste that occurred at UBB was obtained. The results showed that all total waste obtained was Rp. 126,364,598.13 / day in UBB. By asking for alternative improvements, a potential savings value of Rp.74,436,596 / day is obtained.